Screening of basidiomycetes from Amazonia for the production of biotechnological interest enzymes - Souza, Helenires Queiroz de; Oliveira, Luiz Antonio de; Andrade, Jerusa Souza (Ciência e Tecnologia de Alimentos, 2008)
Mushrooms, edible basidiomycetes, have been extensively used as producers of different substances of economical interest, such as enzymes, antibiotics, vitamins, amino acids, and steroids. The objective of this study is to detect the production of enzymes such as amylases, proteases, cellulases, phenoloxidases and pectinases for lineages of basidiomycetes originating from the Amazonian forest. For the production of enzymes, mushrooms were cultivated in a liquid medium with substratum (0,5%), pH adjusted for each enzyme, and incubated at 28 °C, under agitation and 140 rpm for 96 or 120 hours. After this period, the samples were filtered for the separation of the mycelial mass. The filtrates were inoculated in solid medium surface perforated cup-plates of 6 mm diameter, appropriate for the detection of enzymes in Petri dishes. The plates were incubated at 28 °C for 24 hours, for observation to reveal enzymatic halos. It was verified the activity of the amylase and protease produced by the mushrooms grown in the liquid medium, with different nutritive sources. It was possible to detect the cellulase and protease production for all the ones that were isolated, 40% produced amylases, 50% produced phenoloxidases, and 10% produced pectinases. Regarding the activity of the amylase, the wheat bran substrate presented the largest degradation halos revealing Daedalea sp.4E6 and Daedalea sp. 1A, Stereaceae 22B and Pycnoporus sanguineus 12B mushrooms. Considering the substrata tested for protease production, it was observed that the fish protein concentrate was the best. The P. sanguineus 12B, Stereaceae 22B and Cantharellus guyanensis 4Bl mushrooms were the best protease producers.
Seleção de Basidiomycetes da Amazônia para produção de enzimas de interesse biotecnológico
Keywords: Basidiomycota; Cantharellus; Daedalea; Pycnoporus (fungus); Pycnoporus Sanguineus; Stereaceae; Triticum Aestivum